Applications of Pattern Recognition - Travieso-Gonzalez, Carlos M.; Travieso-Gonzalez, Carlos M. (IntechOpen, 2021)
Nowadays, technological advances allow the development of many applications in different fields. In this book, 'Applications of Pattern Recognition' , two important fields are shown. The first field, data analysis, is a good tool to identify patterns; in particular, it is observed by a stereoscopic calculation model based on fixation eye movement, a visual interactive programming learning system, an approach based on color analysis of Habanero chili pepper, an approach for the visualization and analysis of inconsistent data, and finally, a system for building 3D abstractions with wireframes. On the other hand, automatic systems help to detect or identify different kinds of patterns. It is applying to incomplete data analysis a retinal biometric approach based on crossing and bifurcation, an Arabic handwritten signature identification system, and finally, the use of clustering methods for gene expression data with RNA-seq.
English
Keywords: Machine learning